Cyberbullying in China: the connection between language and behaviour - Li, Wan-Qi (2020)
Cyberbullying refers to individual or group behaviours involving the use of offensive language online, and it is a global issue that causes serious social problems. Research on cyberbullying has thus emerged in several fields, such as psychology, sociology, computer science, and linguistics. However, studies of cyberbullying in China have met with limitations and challenges, despite cyberbullying there becoming a serious and prevalent problem, making China a meaningful case study for cyberbullying investigations. This thesis thus used a new combined theoretical framework, a Socio-ecological Framework with Language Feature and Management Approaches, to analyse cyberbullying language features and usages, cyberbullying motivations, and the variables affecting cyberbullying in the Chinese context. Based on its overall findings, this research also made some extrapolations to cognate social issues in order to discuss the consequences of cyberbullying, and to develop potential measures for detecting or regulating cyberbullying. The methodologies selected for this thesis were content analysis, social network analysis, and interviews; thus, the work is both qualitative and quantitative. Content analysis was used to examine cyberbullying language usage, formations, and features using an author-created 2,000-word database. Based on these results, social network analysis was applied to provide deeper insights into how contextual and sociolinguistic variables affect cyberbullying, while the interviews helped to gather additional views on cyberbullying, providing new ways to examine the challenges of regulating cyberbullying, as well as highlighting potential approaches to doing this. The main finding of this thesis is that not all cyberbullying words are inherently offensive; emotional and even ordinary words may have cyberbullying functions in context. Additionally, during cyberbullying, the context for communication, current events, and the forms adopted all affect the use of cyberbullying language. Both males and females both use a range of offensive words in cyberspace, and cyberbullying can affect any internet users, not only minors. The consequences of cyberbullying may also be more serious than those of traditional bullying. These findings were then adopted to draft a set of preliminary measures for addressing cyberbullying.